The Role of Quran Teachers in Eliminating Illiteracy Of The Quran at The Majlis Taklim Bani Tamim in Bugel, Karawaci, Tangerang City - Muhamad Lutfan Fahmi; Mohamad Asrori Mulky (International Research and Development for Human Beings (IRDH), 2025)
This research aims to evaluate the role of Qur'an teachers in addressing illiteracy of the Qur'an in Bugel Karawaci Village, Tangerang City, as well as to identify the factors affecting the effectiveness of programs aimed at combating Qur'anic illiteracy in the community. The research method used is a case study with a qualitative approach. Data was collected through observations, in-depth interviews, and analysis of documentation related to religious study activities. Religious teachers employed the Iqra' method and a personal approach to tackle various learning obstacles faced by the community, especially teenagers, including a lack of self-confidence and limited access to formal education. The findings indicate that religious teachers play a vital role in fostering the community, effectively improving the ability to read the Qur'an. Internal factors such as learning motivation and external factors such as family support and socio-economic conditions significantly influence the success of the program. The conclusion of this study is that religious teachers play a crucial role in improving Quran literacy in the community. However, to achieve more optimal results, better synergy is needed between religious teachers, educational institutions, and families. This study recommends the development of more integrated and adaptive strategies for religious teachers that take into account the specific needs and conditions of the local community.